Longitudinal analysis of Plasmodium falciparum genetic variation in Turbo, Colombia: implications for malaria control and elimination (2015)
ABSTRACT: Background: Malaria programmes estimate changes in prevalence to evaluate their efficacy. In this study, parasite genetic data was used to explore how the demography of the parasite population can inform about the processes driving variation in prevalence. In particular, how changes in treatment and population movement have affected malaria prevalence in an area with seasonal malaria. Methods: Samples of Plasmodium falciparum collected over 8 years from a population in Turbo, Colombia were genotyped at nine microsatellite loci and three drug-resistance loci. These data were analysed using several population genetic methods to detect changes in parasite genetic diversity and population structure. In addition, a coalescent- based method was used to estimate substitution rates at the microsatellite loci. Results: The estimated mean microsatellite substitution rates varied between 5.35 × 10−3 and 3.77 × 10−2 substitutions/ locus/month. Cluster analysis identified six distinct parasite clusters, five of which persisted for the full duration of the study. However, the frequencies of the clusters varied significantly between years, consistent with a small effective population size. Conclusions: Malaria control programmes can detect re-introductions and changes in transmission using rapidly evolving microsatellite loci. In this population, the steadily decreasing diversity and the relatively constant effective population size suggest that an increase in malaria prevalence from 2004 to 2007 was primarily driven by local rather than imported cases.